Isolation and partial characterization of a biosurfactant produced by streptococcus thermophilus A - Rodrigues, L. R. (2006)
Isolation and characterization of the surface active components from the crude biosurfactant produced by Streptococcus thermophilus A was studied. A fraction rich in glycolipids was obtained by the fractionation of crude biosurfactant using hydrophobic interaction chromatography. Molecular (by Fourier transform infrared spectroscopy) and elemental compositions (by X-ray photoelectron spectroscopy) were determined. Critical micelle concentration achieved was 20 g/l, allowing for a surface tension value of 36 mJ/m2. Moreover, this glycolipid rich fraction was found to be an anti-adhesive and antimicrobial agent against several bacterial and yeast strains isolated from explanted voice prostheses. Further purification steps should be carefully analyzed as each purification step will increase the costs and decreases the amounts of biosurfactants recovered.